POLA SEBARAN RUANG AKTIVITAS PKL DI RUANG PUBLIK KAWASAN PECINAN SEMARANG - Retno Widjajanti; Sunarti Sunarti; Wido Prananing Tyas (Diponegoro University, 2017)
Street vendors has grown rapidly in functional areas in Semarang City, such as in Chinatown. Problems arise when street vendors start using public spaces as a place to trade. The sidewalks and roadside used by street vendors for activities disrupt the main function of the public space. This condition occurs because the government does not have a clear reference about the activity space for street vendors. The relocation efforts undertaken by the government have not considered the characteristics and spatial behavior of street vendors so the relocation often fail and street vendors tend to re-trade in the first place. The study of space for street vendors is urgently need, in line with the increasing conflict of space for street vendors in various regions of Indonesia. The purpose of this study is to identify the space livability of street vendors in Pecinan based on the spatial behavior of street vendors. The research used quantitative descriptive method by using questionnaire as data collection technique. The results showed that agglomeration, strategic location, main activity and accessibility are the variables that influence the pattern of spatial distribution of street vendors activity.